Alternative meat industry - Elias, Jaan, (SAGE Business cases., 2021)
In 2009, when experienced entrepreneur Ethan Brown decided to build a better veggie burger, he set his sights on an exceptional goal - create a plant-based McDonald's equally beloved by the American appetite. To do this, he knew he needed to transform the idea of plant-based meat alternatives from the sleepy few veggie burger options in the grocer's freezer case into a fundamentally different product.